2013
DOI: 10.1103/physreve.88.062808
|View full text |Cite
|
Sign up to set email alerts
|

Scaling symmetry, renormalization, and time series modeling: The case of financial assets dynamics

Abstract: We present and discuss a stochastic model of financial assets dynamics based on the idea of an inverse renormalization group strategy. With this strategy we construct the multivariate distributions of elementary returns based on the scaling with time of the probability density of their aggregates. In its simplest version the model is the product of an endogenous autoregressive component and a random rescaling factor designed to embody also exogenous influences. Mathematical properties like increments' stationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…For example, a simple Gaussian random walk is time-reversal invariant (Weiss, 1975 ). Practical implementations of temporal asymmetry measures use, for example, the difference between the probability density functions of the original and time-reversed series, or of their corresponding variances (Zumbach, 2009 , 2012 ), or temporal-based correlation measures over different temporal windows, or between the past and future data blocks of the same temporal length (Zamparo et al, 2013 ), or by using Granger causality (Winkler et al, 2016 ). Time irreversibility is a strong signature of nonlinearity (Schreiber and Schmitz, 2000 ) and is commonly related to entropy production by the underlying (often unknown) mechanism that generated the time series (see Vladimirov and Petersen, 2010 ; Roldán, 2014 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a simple Gaussian random walk is time-reversal invariant (Weiss, 1975 ). Practical implementations of temporal asymmetry measures use, for example, the difference between the probability density functions of the original and time-reversed series, or of their corresponding variances (Zumbach, 2009 , 2012 ), or temporal-based correlation measures over different temporal windows, or between the past and future data blocks of the same temporal length (Zamparo et al, 2013 ), or by using Granger causality (Winkler et al, 2016 ). Time irreversibility is a strong signature of nonlinearity (Schreiber and Schmitz, 2000 ) and is commonly related to entropy production by the underlying (often unknown) mechanism that generated the time series (see Vladimirov and Petersen, 2010 ; Roldán, 2014 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…The main contribution of the present paper is the derivation of closedform formulae for option pricing and associated hedging strategy, based on an equivalent martingale measure. This is obtained by means of a model recently introduced in statistical mechanics by Zamparo et al (2013) whose advantage is to be consistent with the observed features of financial data, thus including non-Gaussian scaling behaviour. The general results provided here include as a special case the BS pricing formula.…”
mentioning
confidence: 70%
“…Upon explicit integration over σ, the endogenous component becomes in this case a genuine ARCH process (see Zamparo et al, 2013) described by…”
Section: Non-gaussian Scaling In Financial Datamentioning
confidence: 99%
“…[26] and systematically exposed in Ref. [27]. It is grounded on a "fine-graining" procedure obtained "inverting" the real space renormalization group (RG hereafter) flow in the space of return probability distributions.…”
Section: Renormalization Groupmentioning
confidence: 99%
“…The merits and challenges of this approach are extensively discussed in Ref. [27]. This approach seems to offer the best setup to frame the probabilistic analysis of (possibly selforganized) critical behavior in time series.…”
Section: Renormalization Groupmentioning
confidence: 99%